Pendampingan dan Pelatihan Penyusunan Bahan Ajar Pendidikan Pancasila dan Kewarganegaraan (PPKn) pada Materi Hukum - Triyanto Triyanto (PKn Progresif: Jurnal Pemikiran dan Penelitian Kewarganegaraan, 2020)
The learning process and learning in education units are expected to always have relevant and adequate learning materials and resources. Relevant and adequate learning resources are a companion tool to achieve learning objectives and graduate competencies that are in accordance with the expected basic competencies. However, the fundamental problem in developing teaching materials experienced by teachers in learning Pancasila and Citizenship Education (PPKn) especially in legal material lies in the limited understanding of knowledge in creating and developing creative and innovative teaching materials by exploring legal materials. For this reason, an effort to increase knowledge and skills in developing teaching materials in learning PPKn is especially needed in legal material. This activity aims to improve the professional competence of teachers in developing PPKn teaching materials on legal material. The results achieved in this mentoring and training improve teacher's knowledge and skills in developing teaching materials which can be seen from the results of the evaluation of activities in the form of tests of material understanding and practice of developing teaching materials on legal material. Keyword: assistance and training, development of teaching materials, legal materials.